Role of Herding Behavior in Influencing Investor Decision Making in India - Agrawal, Dheeraj; Singhal, Tanvi; Santi Swarup, K. (Indian Journal of Research in Capital Markets, 2016)
Herding behavior is the tendency of individual investors in India to follow investment decisions of others. Behavioral finance assumes that characteristics of individual market participants and the structure of information systematically have an influence on investment decisions of individuals. Financial markets have been facing unforeseen and sudden economic turbulences that have been directly or indirectly responsible for returns on stocks. This study aimed to identify the causes of herding behavior by an individualÂ investor and identify the possible effects of herding behavior of investors on the stock market. To do this, we interacted with stock market investors to identify the reasons of their herding behavior. The response collected was analyzed using system dynamics models. The study revealed that investors in India have the tendency to follow the behavior of others while making investments in stock markets in order to avoid losses and regrets. This is because they are not much financially literate and are not well aware about stock market functioning. So, they generally go with the decisions made by market leaders to earn safe returns out of their investments.